IMAGINATIVE COMMUNICATION AND COMMUNITY: THE PHENOMENOLOGICAL-ENACTIVE APPROACH TO THE CO-CONSTITUTION OF PUBLIC PHENOMENA - BRIEDIS, Mindaugas; NAVARRO, Mariano (Studia Universitatis Babeș-Bolyai Philosophia, 2021)
An ever-evolving phenomenological-enactive perspective can expand our reflection on the entanglement between enactive subjects and their living ecologies. This article applies certain classical phenomenological projects and their enactive extension to public phenomena (objects, spaces, events, etc.). As an instance of the embodied cognition discourse, this research also aims to thematize the enactive, affective, and intersubjective aspects of the relation to the (urban) Lebenswelt. This may help in understanding both the potential of the phenomenological-enactive methodology and the processes of an embodied intersubjective co-constitution of a public ethos. Theoretical ideas presented in the article are illustrated with reflections on some concrete public phenomena.